A Worldwide Pharmacoepidemiologic Update on Drug‐Induced Antineutrophil Cytoplasmic Antibody–Associated Vasculitis in the Era of Targeted Therapies. Issue 1 (11th November 2021) - Deshayes, Samuel; Dolladille, Charles; Dumont, Anaël; Martin Silva, Nicolas; Chretien, Basile; De Boysson, Hubert; Alexandre, Joachim; Aouba, Achille
Abstract : Objective: The literature supporting the role of a specific drug in the onset of drug‐induced antineutrophil cytoplasmic antibody–associated vasculitis (AAV) mainly relies on case reports or short series and implicates old treatments. The advent of new treatments may have modified the epidemiology of these adverse drug reactions. This study was undertaken to update the list of drugs associated with AAV by using a pharmacovigilance‐based data mining approach. Methods: We collected data on adverse drug reactions reported using the Medical Dictionary for Regulatory Activities preferred term "anti‐neutrophil cytoplasmic antibody positive vasculitis" up to November 2020 from the World Health Organization pharmacovigilance database (VigiBase). For each retrieved drug, a case–noncase analysis was performed, and disproportionate reporting was calculated by using the information component (IC). A positive IC025 value, which is the lower end of the 95% credibility interval, was considered significant. Results: A total of 483 deduplicated individual case safety reports of drug‐induced AAV involving 15 drugs with an IC025 >0 were retrieved. Of the individuals with drug‐induced AAV for whom data on sex were available (n = 371), 264 (71.2%) were women. The median age at onset of drug‐induced AAV was 62 years (quartile 1 [Q1]–Q3 45–72 years), and the median time from the introduction of the suspected drug to the onset of drug‐induced AAV was 9 months (Q1–Q3 1–36 months). Drug‐induced AAV was considered serious in 472 (98.1%), and was fatal in 43 (8.9%), of 481 cases. The drugs associated with the highest disproportionate reporting were hydralazine, propylthiouracil, thiamazole, sofosbuvir, minocycline, carbimazole, mirabegron, and nintedanib. Conclusion: Our findings strengthen the evidence of an association of AAV with previously suspected drugs, but also identify 3 new drugs that may cause drug‐induced AAV. Particular attention should be given to these drugs by prescribers and in experimental studies.